2020
DOI: 10.5194/egusphere-egu2020-4540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple catchments and where to find them: The storage discharge relationship as a proxy for catchment complexity

Abstract: <p>Hydrology and especially hydrological models often treat catchments as if they were leaky buckets. But, do we find such catchments in the real world or is this just a convenient simplification? Moreover, if we find them, what attributes allow these catchments to show such a simple behavior? To study this, we look at time series of 27 years for 90 catchments in Hesse, Germany, which includes droughts and years of abundant precipitation. In addition, the state Hesse provides a wide range of catc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Non‐linear activation of subsurface pockets, generating a ‘fill‐and‐spill’ subsurface runoff response (Chu et al, 2013; Tromp‐van Meerveld & McDonnell, 2006), was not observed. This finding is not in agreement with the concept of ‘simple catchments’ (Jehn et al, 2021) which attributes the lack of pronounced ‘fill‐and‐spill’ response to ‘simple’ catchments with more preferential flow and not to the ‘complex’ catchments with dominant matrix flow such as Uhlířská. We explain this discrepancy by the hydrological functioning of the riparian wetland.…”
Section: Discussionmentioning
confidence: 56%
“…Non‐linear activation of subsurface pockets, generating a ‘fill‐and‐spill’ subsurface runoff response (Chu et al, 2013; Tromp‐van Meerveld & McDonnell, 2006), was not observed. This finding is not in agreement with the concept of ‘simple catchments’ (Jehn et al, 2021) which attributes the lack of pronounced ‘fill‐and‐spill’ response to ‘simple’ catchments with more preferential flow and not to the ‘complex’ catchments with dominant matrix flow such as Uhlířská. We explain this discrepancy by the hydrological functioning of the riparian wetland.…”
Section: Discussionmentioning
confidence: 56%